Analisis Rasio Keuangan Dalam Mempengaruhi Pertumbuhan Laba Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Indah Novi Wardyani; Sholikha Oktavi Khalifaturofiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This researcher aims to determine Profitability which is influenced by Liquidity, Solvability and Activity. This research uses a quantitative approach to data collection using secondary data. The type of data used in this study uses panel data. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The sampling technique used is Non-Probability Sampling. The data analysis technique used in this research is using descriptive statistical analysis and classical assumption test analysis to examine the effect of more than one independent variable on the dependent variable. The profitability variable does not have a significant effect on profit growth and also liquidity does not have a significant effect on the company's profit growth however, solvency which has a significant positive effect on profit growth and also on the activity variable as measured by the Total Asset Turnover ratio does not have a significant effect on the profit growth of Sub- Manufacturing Companies The Food and Beverage Sector listed on the IDX 2017-2021. Keywords: Profitability, Solvency, Liquidity, Activity